Beneficial effects of silicon in plants under abiotic stress conditions: A new approach - Paiva de Oliveira Moraes, Sâmia (Revista Ciência Agronômica, 2021)
Considering the importance of Silicon (Si) for plants, many studies have focused to evaluate the ability of the elementto alleviate abiotic stress in different species, mainly of agricultural interest. For all species, Si offers a range of benefi ts in reducing theeffects of biotic and abiotic stress, being especially associated with increases in plant biomass. However, after performed a systematicquantitative review of studies linking Si to the relief of abiotic stress in plants, it was demonstrated that there is a reduction in theeffects of Si over time and that the effects of Si were smaller in recent studies. Furthermore, was found that plants under different typesof stress had similar responses to Si, suggesting that abiotic stress relief mechanisms in plants may be common among conditions ofwater stress, salinity, and heavy metals – the main environmental stresses studied in the literature. This study can guide future research,which should not be limited to simply evaluating the existence of any Si stress-relieving effects, but also to understand the variationthat exists in these mechanisms and considered that they depend on the type of stress and the factors involved in reducing these effects.